A pilot study on impact of use of medium molecular weight hydroxyethyl starch in granulocyte apheresis using Spectra Optia. (October 2022) - Mandal, Saikat; Naim, Faran; Kumar, Ranjan; Gupta, Sumant; Gupta, Vibhu Ranjan; Kathuria, Ishita
Abstract: Introduction: Granulocyte transfusion (GT) is a therapeutic option for prolonged neutropenic patients with severe bacterial or fungal infections. Efficient apheresis based granulocyte collection may be better achieved by infusion of high-molecular-weight (HMW) hydroxyethyl starch (HES). But multiple adverse incidents have been reported with HMW-HES. Due to availability issues and adverse incidents related to it, use of HMW-HES has become limited. Few studies have mentioned about medium molecular weight HES (MMW-HES) (130 kDa) as efficient for this purpose with minimal adverse incidents. So, the aim was to assess the impact of the use of MMW-HES in granulocyte apheresis when using Spectra Optia. Methodology: In this observational study, donors who received MMW-HES during granulocyte harvest were included in HES group and another group who did not receive HES were grouped as non-HES. Injection G-CSF 10 microgram/kg and tablet dexamethasone 8 mg given 12 h before for non-HES group and 6 – 8 h in case of HES group blood donors. Number of adverse incidents observed were noted. Donor/procedure parameters were compared using Mann–Whitney U test / unpaired t test. Results: Granulocyte yield was significantly higher in the HES group (2.5 × 10 10 vs. 1.75 × 10 10, p < 0.01) and was attributed to the difference in collection efficiency (22.61% vs. 10.15%, p < 0.01). There were no significant differences in occurrence of adverse events between HES and non-HES groups. Conclusion: Our results clearly indicate that sufficient number of granulocytes can be harvested by using MMW-HES in Spectra Optia apheresis system even after short interval between mobilization to harvest.